2014
DOI: 10.1371/journal.pone.0098822
|View full text |Cite
|
Sign up to set email alerts
|

Supraclavicular Skin Temperature as a Measure of 18F-FDG Uptake by BAT in Human Subjects

Abstract: BackgroundBrown adipose tissue (BAT) has emerged as a novel player in energy homeostasis in humans and is considered a potential new target for combating obesity and related diseases. The current ‘gold standard’ for quantification of BAT volume and activity is cold-induced 18F-FDG uptake in BAT. However, use of this technique is limited by cost and radiation exposure. Given the fact that BAT is a thermogenic tissue, mainly located in the supraclavicular region, the aim of the current study was to investigate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
99
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(109 citation statements)
references
References 26 publications
9
99
1
Order By: Relevance
“…Furthermore, a recent study has shown, that increased supraclavicular ST reflects increased brown adipose tissue (BAT) activity occurring during cold exposure [37,38]. In our study we measured ST not directly in the supra-, but in the infraclavicular skin region, in which BAT activity is also affected by cold exposure [37,39].…”
Section: Seasonal Effects On Diurnal Profilesmentioning
confidence: 89%
“…Furthermore, a recent study has shown, that increased supraclavicular ST reflects increased brown adipose tissue (BAT) activity occurring during cold exposure [37,38]. In our study we measured ST not directly in the supra-, but in the infraclavicular skin region, in which BAT activity is also affected by cold exposure [37,39].…”
Section: Seasonal Effects On Diurnal Profilesmentioning
confidence: 89%
“…In rodent studies, thermographic measurement of BAT activity has been validated against biochemical markers of BAT thermogenesis, such as UCP-1 upregulation [34]. In human studies, Jang et al [17] reported that a temperature difference between the neck and sternum of 0.9 ∘ C had a positive predictive value of 85% for the presence of supraclavicular BAT, Symonds et al [18] recorded rises of 0.5 ∘ C in supraclavicular temperature in children after mild cold exposure, and Boon et al [27] reported a 0.4 ∘ C cold-induced supraclavicular skin temperature rise, which positively correlated with 18 F-FDG-PET/CT quantification of underlying BAT. In the present study all eight subjects who had BAT activation after cold exposure as determined by 18 F-FDG-PET/CT also showed a rise in neck temperature, as determined by thermal imaging during cold exposure, although the correlation between PET-quantified BAT mass and cold-induced neck temperature rise was not significant in the present cohort (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…All 11 subjects (eight BAT-positive and three BAT-negative, as defined by their 18 F-FDG PET/CT characteristics on cold exposure, described above) also underwent thermography of their neck during the three study visits when calorimetry was performed (Figures 1 and S1A, B). A rise in supraclavicular skin surface temperature has previously been shown to indicate underlying BAT thermogenic activity [17,27]. In the BAT-positive group of eight, there was a significant temperature rise in the neck with cold exposure, with a mean increase in temperature between Run A (baseline) and Run C (end exposure) of 0.44 ± 0.08 ∘ C. In contrast, there was no change in supraclavicular neck temperature with cold exposure in the BAT-negative group ( Figure 5A).…”
Section: F-fdg Pet/ctmentioning
confidence: 99%
“…Although, 18 FDG uptake in a fat depot upon cold exposure is still considered the 'gold standard' in identifying BAT, the defining thresholds used in terms of glucose uptake and adipose tissue identification from CT radiodensity vary tremendously (for review see [100,101]). Further, there are studies which have shown 18 FDG PET to be unreliable to measure BAT thermogenesis [42,65].…”
Section: Bat Massmentioning
confidence: 99%